2015
DOI: 10.1111/1750-3841.12945
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical Effects of Increasing Oil Concentrations on Saltiness and Bitterness Perception of Oil‐in‐Water Emulsions

Abstract: Limited research has been done to investigate saltiness and bitterness perceptions of NaCl, KCl, and caffeine in emulsion systems. Saltiness and bitterness intensities of emulsions prepared with different concentrations of oil [0% (that is, solution), 20%, 40%, canola oil] and different concentrations of 3 tastants (NaCl [0.5% to 1.0%], KCl [0.5% to 1.5%], and caffeine [0.05 to 0.15%]) were measured using the Spectrum™ descriptive method (N = 16) and the Electronic-tongue (E-tongue). Linear regression and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Other studies related to this research also reported that as oil phase is increasing, the saltiness of the emulsion is perceived higher (Torrico and Prinyawiwatkul, 2015). Torrico and Prinyawiwatkul (2015) studied that in both NaCl and KCl, the increasing oil concentrations of oil in water emulsion increased the intensity of salty taste at various salt concentrations.…”
Section: Saltiness Perception Of Emulsion With Different Oil Concentrsupporting
confidence: 57%
See 2 more Smart Citations
“…Other studies related to this research also reported that as oil phase is increasing, the saltiness of the emulsion is perceived higher (Torrico and Prinyawiwatkul, 2015). Torrico and Prinyawiwatkul (2015) studied that in both NaCl and KCl, the increasing oil concentrations of oil in water emulsion increased the intensity of salty taste at various salt concentrations.…”
Section: Saltiness Perception Of Emulsion With Different Oil Concentrsupporting
confidence: 57%
“…Torrico and Prinyawiwatkul (2015) studied that in both NaCl and KCl, the increasing oil concentrations of oil in water emulsion increased the intensity of salty taste at various salt concentrations. Lawrence et al (2012) evaluated the effect of composition and texture of emulsion in solid lipoprotein matrices towards the saltiness perception.…”
Section: Saltiness Perception Of Emulsion With Different Oil Concentrmentioning
confidence: 99%
See 1 more Smart Citation
“…After duplicates removal, abstract article record and backward searching yielded 169 articles. After full‐text record, a total of 111 articles remained for complete data extraction . Among them, we identified 23 studies as having a controlled protocol (including two studies with a randomisation process .…”
Section: Resultsmentioning
confidence: 99%
“…This technique is widely used for meat (Zhang et al ., ), bread (Bolhuis et al ., ) and dairy (Grummer et al ., ) among many products. Other approaches for salt reduction include using flavour enhancers in meat products (Campagnol et al ., ), using non‐homogenous spatial salt distribution in bread (Noort et al ., ) and hot snacks (Emorine et al ., ), and modification of food structure such as in an oil‐in‐water emulsion model (Torrico & Prinyawiwatkul, ; Torrico et al ., ,b).…”
Section: Introductionmentioning
confidence: 99%